Advances in Understanding the Physiological and Molecular Responses of Sugar Beet to Salt Stress - Lv, Xiaoyan; Chen, Sixue; Wang, Yuguang (Frontiers in Plant Science, 2019)
Soil salinity is a major environmental stress on crop growth and productivity. A better understanding of the molecular and physiological mechanisms underlying salt tolerance will facilitate efforts to improve crop performance under salinity. Sugar beet is considered to be a salt-tolerant crop, and it is therefore a good model for studying salt acclimation in crops. Recently, many determinants of salt tolerance and regulatory mechanisms have been studied by using physiological and ‘omics approaches. This review provides an overview of recent research advances regarding sugar beet response and tolerance to salt stress. We summarize the physiological and molecular mechanisms involved, including maintenance of ion homeostasis, accumulation of osmotic-adjustment substances, and antioxidant regulation. We focus on progress in deciphering the mechanisms using ‘omic technologies and describe the key candidate genes involved in sugar beet salt tolerance. Understanding the response and tolerance of sugar beet to salt stress will enable translational application to other crops and thus will have significant impacts on agricultural sustainability and global food security.